Взаимодействие плазменных и дефектных мод в одномерной дефектной диэлектрической слоисто-периодической структуре, граничащей с плазмоподобной средой - Белецкий, Н.Н.; Борисенко, С.А.; Гвоздев, Н.И. (Радіофізика та електроніка, 2013)
В данной работе на основе численного решения дисперсионного уравнения исследованы TM-электромагнитные волны в одномерной дефектной диэлектрической слоисто-периодической структуре, граничащей с плазмоподобной средой. Изучены дисперсионные и энергетические свойства плазменных и дефектных мод в зависимости от положения дефектного слоя в слоисто-периодической структуре. Предсказан эффект резонансного взаимодействия плазменных и дефектных мод. Показана возможность возбуждения электро-магнитных волн в дефектной слоисто-периодической структуре методом нарушенного полного внутреннего отражения. Результаты исследования существенно расширяют представление о характере распространения электромагнитных волн в дефектных слоисто-периодических структурах и могут быть использованы для создания новых типов волноведущих структур, используемых в современных устройствах обработки сигналов в СВЧ и оптическом диапазоне длин волн. У цій роботі на основі числового рішення дисперсійного рівняння вивчаються TM-електромагнітні хвилі в одновимірній дефектній діелектричній шарувато-періодичній структурі, що межує з плазмоподібним середовищем. Вивчено дисперсійні та енергетичні властивості плазмових та дефектних мод в залежності від положення дефектного шару в шарувато-періодичній структурі. Передбачено наявність ефекту резонансної взаємодії плазмових та дефектних мод. Показано можливість збудження електромагнітних хвиль у дефектній шарувато-періодичній структурі методом порушеного повного внутрішнього відбиття. Результати досліджень істотно розширюють уявлення про характер поширення електромагнітних хвиль у дефектних шарувато-періодичних структурах і можуть бути використані для створення нових типів хвилепровідних структур, що використовуються в сучасних пристроях обробки сигналів в НВЧ та оптичному діапазоні довжин хвиль. The defective layered periodic structures (defective photon crystals), bordering upon plasma-like media (semiconductors and metals), arouse considerable interest. This is due to the fact that in such structures there are electromagnetic waves of different types. The properties of these waves have not been adequately investigated yet. The TM-electromagnetic waves in the one-dimension defective dielectric layered periodic structure, bordering upon a plasma-like medium, are studied in this paper on the basis of the numerical solution of the dispersion equation. The dispersion and energy properties of the plasma and defective modes are investigated depending on the location of the defective layer in the layered periodic structure. The effect of the resonant interaction of plasma and defective modes is predicted. The possibility for exciting electromagnetic waves in a defective layered periodic structure by the frustrated total internal reflection is shown. The results of investigations give some ideas of the nature of propagating electromagnetic waves in defective layered periodic structures and they can be used for developing new types of the waveguide structures used in up-to-date devices of signal processing in microwave and optical wave bands